1974
DOI: 10.1126/science.186.4169.1126
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Spine "Dysgenesis" and Mental Retardation

Abstract: Golgi studies reveal abnormally long, thin spines and the absence of short, thick spines on dendrites of cortical neurons in retarded children with normal karyotypes. The degree of dendritic spine loss and abnormality appears to be related to age and the severity of developmental retardation. Dendritic spine "dysgenesis" is a common feature of the microstructural pathology that occurs in profound mental retardation of unknown etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
217
0
3

Year Published

1977
1977
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(233 citation statements)
references
References 11 publications
13
217
0
3
Order By: Relevance
“…The involvement of FMRP in synaptic plasticity was first indicated by the observation of abnormally long dendritic spines with increased density in fragile X patients, which is consistent with the idea that DENDRITIC SPINE DYSGENESIS is associated with human mental retardation [14,50]. Studies in both Fmr1-knockout mice and dfmr1-mutant flies have confirmed that abnormal development of dendritic spines is associated with the loss of FMRP [15,31].…”
Section: Ti Bssupporting
confidence: 56%
“…The involvement of FMRP in synaptic plasticity was first indicated by the observation of abnormally long dendritic spines with increased density in fragile X patients, which is consistent with the idea that DENDRITIC SPINE DYSGENESIS is associated with human mental retardation [14,50]. Studies in both Fmr1-knockout mice and dfmr1-mutant flies have confirmed that abnormal development of dendritic spines is associated with the loss of FMRP [15,31].…”
Section: Ti Bssupporting
confidence: 56%
“…High synaptic density of parallel fiber synapses, tagether with thick and numerous spiny branchlets and spines with extremely thin stalks, would explain the very large logical capacities of Purkinje cells in lobule VIa (Shepherd 1974). Changes in spine shape tending towards swollen head and thin stalk are concomitant to the effects of enhanced presynaptic stimulation (V an Harreveld and Fifkova 1975), and long thin spines are discussed as possible pathogenetic factors in mental diseases (Marin-Padilla 1974;Purpura 1974). The Purkinje cell spines serve as a current-injecting mechanism and spike-blocking device (Llinas and Hillman 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Les synapses excitatrices prennent la forme d'épines faisant saillie sur les dendrites des neurones. Comme la DI affecte les processus cognitifs, il n'est pas surprenant que le nombre et/ou la forme des épines soient altérés dans plusieurs formes de DI [2]. En fait, il est raisonnable de postuler qu'un grand nombre de gènes atteints dans la DI agissent au sein de cascades qui convergent pour moduler la plasticité des synapses.…”
Section: Nouvelleunclassified
“…Les patients atteints de cette maladie présentent des troubles gastro-intestinaux, des problèmes de déglutition, des crises de vomissements, de l'hypotonie et de l'instabilité thermique [1]. Ces patients sont également sujets à des crises dysautonomiques durant lesquelles certaines régions de leur cortex cérébral présentent une activité neuronale anormale [2]. La cause moléculaire de cette maladie est une mutation ponctuelle du gène IKBKAP (inhibitor of kappa light polypeptide gene enhancer in B-cells, kinase complex-associated protein) qui code pour la protéine Elp1, laquelle est requise pour l'assemblage du complexe Elongator.…”
Section: Nouvelleunclassified